2004
DOI: 10.1590/s0103-64402004000200010
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Polishing of dental prostheses can cause a dangerous cycle of cross-contamination involving dentists, laboratory technicians, patients and auxiliary personnel. The aim of this study was to show the microbial contamination in the dental laboratory during the polishing procedure of complete dentures. For this purpose, 4 experiments were conducted. Experiment I -Determination of the total colonyforming units (CFU) counts contaminating complete maxillary dentures. During the polishing procedure, determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…In the present study, 96.2% of the sample taken from the laboratory showed microbial contamination signs. A previous research has reported that dental polishing is a source of infection transmission [24]. In a study on cross-infection in prosthodontics laboratories, it was found that they were substandard in this respect and there was no protocol or training program to limit cross-infection in these laboratories [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 96.2% of the sample taken from the laboratory showed microbial contamination signs. A previous research has reported that dental polishing is a source of infection transmission [24]. In a study on cross-infection in prosthodontics laboratories, it was found that they were substandard in this respect and there was no protocol or training program to limit cross-infection in these laboratories [25].…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the influence of chemical disinfection of CS coated PMMA and PETG materials in order to pursue international recommendations and to reduce cross contamination risks [24,25,26]. All three stated null hypotheses had to be fully or partly rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical splints and dentures are commonly prepared in a dental laboratory. To minimize the risk of cross contamination all dentures, and prosthodontic materials prepared in a dental laboratory or transported between a laboratory and a dental practice, have to be sterilized or disinfected [24,25,26]. Steam sterilization in an autoclave is a common method for medical/dental devices, but it is limited to heat and moisture resistant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan araştırmalarda; diş laboratuvarlarından kliniklere gelen protezlerin yarısından fazlasının bakteriler ile kontamine olduğu (6) ve yine tamir edilmek üzere laboratuvarlara gönderilen kırık protezlerin %90'ının laboratuvarda patojenlerle kontamine olduğu bildirilmiştir (7). Bunların yanı sıra laboratuvarlarda kullanılan pomzaların; mikrokoklar, pseudomonas, kandida ve diğer mantarlar, alkalijenler, Gram-negatif acinetobacter basilleri gibi bakterilerle büyük ölçüde kontamine olduğu gösterilmiştir (8,9). Bu nedenle kliniklerden gelen materyallerin yanı sıra laboratuvarda hazırlanmış olan diş protezleri, indirekt restorasyonlar, implant parçaları ve diş tedavi apareyleri gibi materyallerin de hastalara teslimi öncesinde dezenfekte edilmeleri gerekmektedir (10).…”
Section: Introductionunclassified